FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS HIDUP PASIEN PENYAKIT GINJAL KRONIS YANG MENJALANI HEMODIALISA DI RSU WIRADADI HUSADA BANYUMAS - Kurniawan, Eko Ully; Ma'rifah, Atun Roudotul; Haniyah, Siti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Chronic kidney disease is a progressive and irreversible impairment of kidney function that leads to a decrease in the body’s ability to maintain metabolism as well as fluid and electrolyte balance. One of the therapies performed to sustain the patient’s life is hemodialysis. Patients undergoing hemodialysis experience various physical, psychological, social, and economic changes that may affect their quality of life. This study aimed to determine the factors associated with the quality of life among patients with chronic kidney disease undergoing hemodialysis at Wiradadi Husada General Hospital, Banyumas. The study employed a descriptive correlational design with a cross-sectional approach. The population consisted of 49 patients undergoing routine hemodialysis, selected using the total sampling technique. The research instrument used was the Kidney Disease Quality of Life Short Form 36 (KDQOL-SF 36) questionnaire. Data were analyzed using the Spearman rank correlation test. The results showed that there was no significant relationship between age, education level, blood pressure, duration of hemodialysis, and hemoglobin levels with quality of life (p > 0,05). However, there was a significant relationship between employment status and quality of life (p < 0,05). It can be concluded that employment status is significantly associated with the quality of life of patients with chronic kidney disease undergoing hemodialysis. Therefore, healthcare professionals are expected to provide psychosocial support and motivation to help patients remain productive and improve their overall quality of life